Welfare Lobby Groups responding to Globalisation: A Comparison of the Australian Council of Social Service (ACOSS) and the UK Child Poverty Action Group (CPAG) - Philip Mendes (Social Work and Society)
The past decade has witnessed a period of intense economic globalisation. The growing significance of international trade, investment, production and financial flows appears to be curtailing the autonomy of individual nation states. In particular, globalisation appears to be encouraging, if not demanding, a decline in social spending and standards. However, many authors believe that this thesis ignores the continued impact of national political and ideological pressures and lobby groups on policy outcomes. In particular, it has been argued that national welfare consumer and provider groups remain influential defenders of the welfare state. For example, US aged care groups are considered to be particularly effective defenders of social security pensions. According to this argument, governments engaged in welfare retrenchment may experience considerable electoral backlash (Pierson 1996; Mishra 1999). Yet, it is also noted that governments can take action to reduce the impact of such groups by reducing their funding, and their access to policy-making and consultation processes. These actions are then justified on the basis of removing potential obstacles to economic competitiveness (Pierson 1994; Melville 1999).